2017
DOI: 10.1111/famp.12334
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot of a Brief Positive Parenting Program on Children Newly Diagnosed with Autism Spectrum Disorder

Abstract: Disruptive behaviors can be of comparable or greater concern to parents than the core symptoms of Autism Spectrum Disorder (ASD). Provision of effective interventions to address these behaviors within the first year of initial diagnosis holds great potential for improving the child's, parents', and family's functioning. We piloted a four-session, manualized, positive parenting program on 21 parents of newly diagnosed children ages 2 through 12 years using a mixed methods design. Seventy-five percent of parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
2
10
0
6
Order By: Relevance
“…It could be this individualized aspect of intervention which better equips parents, resulting in improved parenting confidence. In support of this notion, two trials of PCSSTP (Tellegen & Sanders, 2014;Zand et al, 2017) also display the largest effect sizes for parenting stress in this review. Upon removal of Whittingham et al, heterogeneity reduced to non-significance and BPIs had a moderate effect on parenting efficacy (SMD = 0.60).…”
Section: Discussionsupporting
confidence: 65%
“…It could be this individualized aspect of intervention which better equips parents, resulting in improved parenting confidence. In support of this notion, two trials of PCSSTP (Tellegen & Sanders, 2014;Zand et al, 2017) also display the largest effect sizes for parenting stress in this review. Upon removal of Whittingham et al, heterogeneity reduced to non-significance and BPIs had a moderate effect on parenting efficacy (SMD = 0.60).…”
Section: Discussionsupporting
confidence: 65%
“…A study in Australia of Stepping Stones Triple P, a brief individualized parenting program adapted for ASD, reported significant effects with 64 parents on their parenting confidence, and parental stress, parental conflict, and relationship happiness (Tellegen and Sanders 2014). Likewise Zand et al (2018) piloted a four-session, manualized, positive parenting program on 21 parents of newly diagnosed children aged 2 through 12 years and reported clinically and statistically significant reductions in child maladaptive behaviors, as well as improvements in parental and family functioning. In India, Manohar et al (2019) reported that 26 parents who received five, out-patient sessions focusing on social and adaptive skills reported more improvements in parental stress and child outcome measures compared to 24 parents in a control group.…”
mentioning
confidence: 99%
“…Les résultats d'études récentes ont permis de documenter les effets de ces programmes de formation sur le développement et les comportements de l'enfant ainsi que sur les interactions parent-enfant et le fonctionnement familial (Bearss, Burrell, Stewart et Scahill, 2015 ;Brookman-Frazee, Vismara, Drahota, Stahmer et Openden, 2015). D'autres études montrent que ce type de formation, soit l'entrainement parental, a des effets positifs sur la généralisation des apprentissages des enfants, les compétences parentales, les relations parent-enfant, le bien-être des parents, leur sentiment de contrôle (Cappe et al, 2012 ;Rattaz, Alcaraz-Darrou et Baghdadli, 2016) et le sentiment d'efficacité parentale (Zand et al, 2018). Outre les trois programmes en français recensés par Sankey, Derguy, Clément, Ilg et Cappe (2019), il n'en demeure pas moins, que peu de programmes francophones destinés à ces parents ont fait l'objet d'une évaluation de la fidélité d'implantation.…”
Section: Programmes De Formation Parentaleunclassified